Pendidikan Islam dalam Perspektif Masyarakat Petani Madura - Usman Usman (UIN Sunan Ampel Surabaya, 2018)
This article explores perspectives of peasant community in Pamekasan Regency Madura regarding Islamic education as constructed reality. The peasants consider the obligatory of pursuing such education for their children’s Islamic morality in their future. They put first priority in the Islamic education rather than hustling about what profession their children are going to have. This indicates that social construction in a community has uniqueness for the development of child education in every phase. Findings show that spiritual-based parenting, environment positive attitude, and community acceptance to the children develop concept of self, which has implication to the development of children Islamic morality.